1.y=x^2+nx+m=(x+n/2)^2+m-n^2/4在x=-n/2处有最小值m-n^2/4所以-n/2=-1,m-n^2/4=1,得n=2,m=22.y=ax^2+2ax-1=a(x+1)^2-1-a有最大值则a<0,在x=-1处取最大值-1-a=1,a=-23.设此函数为y=a(x-2)^2+5当x=0时,y=1,即4a+5=1,a=-1所以y=-(x-2)^2+5=-x^2+4x 展开
1.y=x^2+nx+m=(x+n/2)^2+m-n^2/4在x=-n/2处有最小值m-n^2/4所以-n/2=-1,m-n^2/4=1,得n=2,m=22.y=ax^2+2ax-1=a(x+1)^2-1-a有最大值则a<0,在x=-1处取最大值-1-a=1,a=-23.设此函数为y=a(x-2)^2+5当x=0时,y=1,即4a+5=1,a=-1所以y=-(x-2)^2+5=-x^2+4x+14.f(2x+1)=x^2-2x=(1/4)(2x+1)^2-(3/2)(2x+1)+5/4所以f(x)=(1/4)x^2-(3/2)x+5/4=(1/4)(x-3)^2-1所以最小值为-15.设y=ax^2+bx+1x=1,y=0:a+b+1=0x=-1,y=6:a-b+1=6 解得:a=2,b=-3所以y=2x^2-3x+1 收起